2005
DOI: 10.1088/0953-8984/17/38/002
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of a high-pressure synthesized compound PtC

Abstract: First-principles density-functional method is used to study the recently high-pressure synthesized compound PtC. It is confirmed by our calculations that the platinum carbide has a zinc-blende ground-state phase at zero pressure and the rock-salt structure is a high-pressure phase. The theoretical transition pressure from zinc-blende to rock-salt is determined to be 52GPa. Furthermore, our calculation shows the possibility that the experimentally synthesized PtC by Ono et al. under high pressure condition migh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…An important problem is the effect of carbon nonstoichiometry on the stability and properties of the others possible polymorphs of platinum metals carbides, which are now predicted [10][11][12][13][14][15][16][17][18], as well as the studying of other possible compositions (M/C ratios)-in comparison with examined in the present work. In the last case the so-called semi-carbides with stoichiometry M 2 C are especially interesting, as related semicarbides have been often found in the systems M-C, where M are d metals of IV-VII sub-groups, see [4][5][6]44].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…An important problem is the effect of carbon nonstoichiometry on the stability and properties of the others possible polymorphs of platinum metals carbides, which are now predicted [10][11][12][13][14][15][16][17][18], as well as the studying of other possible compositions (M/C ratios)-in comparison with examined in the present work. In the last case the so-called semi-carbides with stoichiometry M 2 C are especially interesting, as related semicarbides have been often found in the systems M-C, where M are d metals of IV-VII sub-groups, see [4][5][6]44].…”
Section: Discussionmentioning
confidence: 93%
“…Alongside the nitrides mentioned above, a series of investigations of noble metal carbides also has been carried out [9][10][11][12][13][14][15][16][17][18][19][20][21]. The most extensively examining material among them is platinum carbide (PtC), which was successfully synthesized at high pressure and high temperature by the laser-heated diamond anvil cell technique [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al [25] have given a first-principles calculation of PtC. They preferred PtC crytallized in zinc-blende (ZB) structure since their results showed that the RS-PtC is mechanically unstable.…”
mentioning
confidence: 99%
“…Fan et al [2] suggested that among OsC, IrC, PtC with the rocksalt (NaCl) structure only PtC is elastically stable. Li et al [3] and Peng et al [4] predicted that the zincblende (ZnS) structure is more stable phase for PtC. It is known that due to the large mass difference between Pt and C, the only X-ray diffraction analysis is not sufficient to distinguish ZnS and NaCl structures from each other.…”
Section: Introductionmentioning
confidence: 99%